Framing effects and impatience: Evidence from a large scale experiment - Eline van der Heijden; Tobias J. Klein; Wieland Müller; Jan Potters (Institute for the Study of Labor (IZA), 2012)
We confront a representative sample of one 1,102 Dutch individuals with a series of incentivized investment decisions and also elicit their time preferences. There are two treatments that differ in the frequency at which individuals decide about the invested amount. The low frequency treatment stimulates decision makers to frame a sequence of risky decisions broadly rather than narrowly. We find that the framing effect is significantly larger for impatient than for patient individuals. This result is robust to controlling for various economic and demographic variables and for cognitive ability.
Keywords: C93; D03; D81; 330; framing; choice under risk; time preference; experiment; Entscheidung bei Risiko; Framing; Zeitpräferenz; Test; Niederlande